1999
DOI: 10.1038/sj.bjc.6690594
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte nadir as a marker for chemotherapy efficacy in node-positive breast cancer treated with adjuvant CMF

Abstract: SummaryThe purpose of this study was to examine the association between the leucocyte nadir and prognosis in breast cancer patients receiving adjuvant chemotherapy consisting of cyclophosphamide, methotrexate and fluorouracil (CMF). Three hundred and sixty-eight patients with node-positive breast cancer without distant metastases were treated with six cycles of adjuvant CMF. Some patients (n = 60) also received tamoxifen. All patients underwent surgery and received radiotherapy to the axillary and supraclavicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 24 publications
5
66
0
3
Order By: Relevance
“…Since the late 1990s, several studies have linked myelosuppression induced by adjuvant chemotherapy to a better outcome in patients with breast cancer (Saarto et al, 1997;Poikonen et al, 1999;Mayers et al, 2001;Cameron et al, 2003). Recently, Di Maio et al (2005) reported the first evidence regarding the relationship between chemotherapy-induced neutropenia and longer survival time in patients with an advanced stage of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the late 1990s, several studies have linked myelosuppression induced by adjuvant chemotherapy to a better outcome in patients with breast cancer (Saarto et al, 1997;Poikonen et al, 1999;Mayers et al, 2001;Cameron et al, 2003). Recently, Di Maio et al (2005) reported the first evidence regarding the relationship between chemotherapy-induced neutropenia and longer survival time in patients with an advanced stage of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The survival curves of the four categories were estimated by the Kaplan -Meier method and compared by the log-rank test. This approach, considering the occurrence of myelosuppression during chemotherapy to be a baseline feature, has been used in many studies (Saarto et al, 1997;Poikonen et al, 1999;Cameron et al, 2003;Nakata et al, 2006) and is appropriate in an adjuvant setting, as the number of patients who die during the chemotherapy treatment period is usually negligible. In advanced cancer, however, considering myelosuppression to be a baseline feature can lead to a large bias because fewer cycles of chemotherapy can be administered due to poorer outcomes, consequently leading to a lower chance of neutropenia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been confirmed by other retrospective studies using either CMF (Mayers et al, 2001) or anthracyclinebased regimens (Chirivella et al, 2006). Moreover, numerous retrospective studies suggested that early breast cancer patients who experienced the greater myelosuppression related to adjuvant chemotherapy have a trend towards a better outcome (Saarto et al, 1997;Colleoni et al, 1998;Poikonen et al, 1999;Mayers et al, 2001;Cameron et al, 2003). Additionally, prospective studies demonstrated that an increase in chemotherapy RDI resulted in an improvement of DFS and OS (Budman et al, 1998;Citron et al, 2003;Bonneterre et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy induced leucopenia (CIL) is a common and significant adverse effect of chemotherapy, defined as a leucopenia count of <4.00×10 9 /L, and it can put patients at risk for severe infection (Lyman et al, 2010;Lyman and Kleiner, 2011). It is also the major dose-limiting toxicity, and it is frequently managed by reducing or delaying the chemotherapy (Delbaldo et al, 2004;Hangaishi, 2011;Saloustros et al, 2011), which can result in lower diseasefree and overall survival (Kvinnsland et al, 1999;Gurney Schiller et al, 2002;Pfister et al, 2004), However, research (Shitara et al, 2011) on breast cancer (Saarto et al, 1997;Poikonen et al, 1999;Cameron et al, 2003;Shitara et al, 2010;Han et al, 2012), small-cell lung cancer (Banerji et al, 2006), osteosarcoma (Ratain, 1998), ovarian cancer (Sawyer and Ratain., 2001) have shown the association between chemotherapy-induced neutropenia and better clinical outcome for patients. It is not associated with increased risk for death (Souza-Dantas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%